Enhancement of the photochromic switching speed of bithiophene azo dyes - Coelho, Paulo J. (2012)
A series of heteroaryl substituted bithiophene azo dyes in solution were irradiated with visible light to promote the azo E–Z isomerization and then the kinetics of the thermal Z–E back reaction was studied. The speed of this process is strongly influenced by the nature of the aromatic ring linked to the N=N function.While thiazole bithiophene azo dyes exhibit high switching speeds between the two isomers, but limited interconversion, for benzothiazole and substituted thiadiazole bithiophene azo dyes the switching between the two photoisomers can be performed in 3 s with a significant conversion of the transisomer to the thermal unstable cis-isomer (19–21%) and therefore a notable variation of the visible spectrum is observed.